Znaczenie snu i sposoby poprawy jego jakości u sportowców = Impact of sleep and methods to improve its quality in the context of sporting activities - Frydrych-Szymonik, Aleksandra; Augustyn, Gabriela; Szyguła, Zbigniew (Journal of Education, Health and Sport, 2016)
Frydrych-Szymonik Aleksandra, Augustyn Gabriela, Szyguła Zbigniew. Znaczenie snu i sposoby poprawy jego jakości u sportowców = Impact of sleep and methods to improve its quality in the context of sporting activities. Journal of Education, Health and Sport. 2016;6(5):157-176. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.51416 http://ojs.ukw.edu.pl/index.php/johs/article/view/3518 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.04.2016. Revised 29.04.2016. Accepted: 12.05.2016. Znaczenie snu i sposoby poprawy jego jakości u sportowców Impact of sleep and methods to improve its quality in the context of sporting activities Aleksandra Frydrych-Szymonik1, Gabriela Augustyn1, Zbigniew Szyguła2 Aleksandra Frydrych-Szymonik1, Gabriela Augustyn1, Zbigniew Szyguła2 1Studia doktoranckie, Wydział Wychowania Fizycznego, Akademia Wychowania Fizycznego w Krakowie, 2Zakład Medycyny Sportowej i Żywienia Człowieka, Wydział Wychowania Fizycznego i Sportu, Akademia Wychowania Fizycznego w Krakowie 1Doctoral studies, Faculty of Physical Education, The University of Physical Education in Krakow 2Section of Sports Medicine and Human Nutrition, Faculty of Physical Education and Sport, The University of Physical Education in Krakow Aleksandra Frydrych-Szymonik, afrydrychszymonik@gmail.com, tel. 601 146 509 AWF w Krakowie, Al. Jana Pawła II 78, 31-571 Kraków Słowa kluczowe: deficyt snu, drzemka, odnowa biologiczna sportowców, używki Key words: sleep disorders, nap, athletic recovery, drugs Streszczenie Cel Pracy Celem pracy było określenie znaczenia snu i wskazanie sposobów poprawy jego jakości u sportowców na podstawie przeglądu piśmiennictwa naukowego. Materiał i Metody Do analizy wybrano zagraniczne artykuły opublikowane w latach 2005 do 2015, korzystając z bazy danych: Medline EBSCO, Medline Ovid, PubMed oraz internetową wyszukiwarkę artykułów naukowych – Google Scholar. W przeglądzie uwzględniono prace oryginalne, zawierające w temacie (subjects) pojęcia: „sleep” i „athletes”. Z analizy wykluczono prace dotyczące medycznych zaburzeń snu oraz te, które nie mają związku ze sportem. Wyniki Zaburzenia snu stają się coraz częstszą przyczyną obniżania sprawności psychofizycznej zawodników, a biorą się one głównie z niewielkiej wiedzy na temat higieny snu. Zbyt mała liczba godzin snu powoduje szereg negatywnych zmian w organizmie, co w konsekwencji ma związek z obniżeniem zdolności wysiłkowej sportowców. Wnioski Należy dbać o prawidłową jakość i ilość snu oraz wprowadzać odpowiednio zaplanowane drzemki regeneracyjne w odnowie biologicznej zawodników. W działaniach optymalizujących sen sportowców należy również brać pod uwagę fakt, iż dieta, nawyki żywieniowe oraz używki mają znaczący wpływ na jakość i ilość snu człowieka. Abstract The aim of the study was to define the impact of sleep and identify methods to improve its quality in athletes , drawing on a review of the scientific literature. Methods Foreign literature published from 2005 to 2015 was reviewed using the following databases: Medline, PubMed and Google Scholar. The review included original papers, containing in the title the following expression: "sleep" and "athletes". The analysis excluded articles about the sleep disorders and articles not related to sports. Results Sleep disorders have had an increasingly negative impact on the psychophysical abilities of athletes, and they are mainly caused by little knowledge of the sleep hygiene. An insufficient amount of sleep brings about a number of changes to the human body that can have a negative impact which implies a decrease of athletic performance. Conclusion Proper quality and amount of sleep must be ensured, and duly scheduled regeneration naps have to be introduced in the recovery of athletes. In order to optimize the sleep of athletes, the effect of diet, nutrition habits and stimulants on the quality and amount of sleep has to be taken into consideration.